Extração seletiva de metais pesados em sedimentos de fundo do Rio Tietê, São Paulo Selective extraction of heavy metals in bottom sediments from Tietê River, São Paulo - José Eduardo Bevilacqua; Ivone Silveira da Silva; Jaim Lichtig; Jorge César Masini (Química Nova, 2009)
Sediment samples from Tietê river were submitted to chemical and sequential extractions of heavy metals (Cd, Cr, Cu, Ni, Pb and Zn). It was followed a single extraction by using 0.1 mol L-1 hydrochloric acid and a sequential procedure to evaluate possible chemical associations described as exchangeable, carbonate, reducible oxides, sulfide, organic matter and residual fractions. High concentrations of heavy metals were determined at Pirapora reservoir, which is closer to the Metropolitan Area of São Paulo while for Barra Bonita reservoir, the results showed low concentrations for such elements. Acid volatile sulfides, grain size distribution and carbon contents were also determined.